The Basic questions of oncogynecology: textbook for medical students, clinical residents, continuing medical education participants, graduate students, doctoral candidates and oncologists, obstetricians and gynecologistsОсновные вопросы онкогинекологии: учебник для иностранных студентов образовательных учреждений, реализующих программы высшего образования по специальности 31.05.01 "Лечебное дело" по дисциплине "Акушерство и гинекология", а также для клинических ординаторов иностранных факультетов, обучающихся по специальности 31.08.01 "Акушерство и гинекология" - Кира, Е. Ф. военная медицина, акушерство и гинекология 19590403 Евгений Федорович (Textbook, 2018)
The textbook encapsulates the epidemiology, etiology and pathogenesis of malignant tumors of femalegenitals and describes the modern examination techniques allowing to obtain objective information onpatient's condition. The issues of early diagnosis, treatment and prevention of oncological diseases in women are discussed. The book is useful for medical students, clinical residents, continuing medical education participants, graduate students, doctoral candidates and oncologists, obstetricians and gynecologists.